POLÍTICAS PÚBLICAS, FEDERALISMO E DIMENSÕES JURÍDICO-POLITICAS DA JUSTIÇA SOCIAL: Análise do Plano Plurianual 2014-2017 do Munícipio de Cruz Machado - Paraná - Zakseski, Francieli Aparecida (2021)
The present study analyzes the elaboration process and the content of the PPA 2014- 2017 of the government of the Municipality of Cruz Machado - Paraná. Thus, the persistence of this research sought to observe the real and analyze the proposals of the government plan that has the potential to contribute to the development under the legal-political dimension of social justice in the aforementioned locality. The description highlights the procedures of the municipal Executive and Legislative powers for the elaboration and approval of the PPA, as to the form chosen for the plan's processing and discussion, and, mainly, seeks to recognize which public policies have been implemented in the location, considering the perception of the political agents and subjects inserted in society, and their impact. To this end, a qualitative field study was carried out, using bibliographic and documentary sources and semi-structured interviews, which were analyzed based on the assumptions of Critical Discourse Analysis (CDA) Fairclough (2001). From the analysis of the research data, it can be seen that the Brazilian legal system ensures the requirement of popular participation in decisions and preparation of the public budget, by holding at least one public hearing in the process, however, the procedures have limited scope, mainly due to the power relations that are rooted in the political-economic structure of society, Since, although there is room for participation, for economic, social and cultural reasons this participation is treated as mandatory under a perspective of normative control under those who have direct connection with the public bodies and due to the existence of institutionalized standards that symbolically place the population in an inferior position to those responsible for preparing the plan. Moreover, when the PPA is not built on effectively participatory and democratic bases it may not be able to contemplate all the needs of the population and a development based on criteria of social justice. The public policies prioritized by state action also depend on the social context and especially on the relations of forces and pressure groups that permeate the context of the construction of the PPA and cross the State, since the State does not totally ignore the needs of the population, thus maintaining the balance and status quo.